Pengaruh Total Harmonic Distortion (THD) Terhadap Pembacaan kWh Meter Semi Digital - Surapati, Alex; Panggabean, Martin; Rosa, Muhammad Khairul Amri (UNIB Press, 2022)
AbstrakEnergy measurement using a kWh meter must have good accuracy. The increasing use of non-linear electrical equipment causes harmonics in the network. This study aims to measure and analyze voltage, current, power, power factor and the percentage of Total Harmonic Distortion (THD). The research was carried out by designing and making a device in the form of an electrical circuit connected to a semi-digital kWh meter with a fixed load of 10 incandescent lamps with a power of 100 watts each and 1 single-phase induction motor. The test results show that the incandescent lamp load test produces a THD-I percentage of 3.5% and a THD-V percentage of 3.7% with a measurement error value of 0.675%. In the motor load test, the percentage of current harmonics becomes high at 16.6% and the THD-V percentage is 3.4% and the measurement error value is 3.48%. In testing the variation of the load combination of an induction motor and incandescent lamps, the percentage of THD-I is 5.8% and the percentage of THD-V is 3.2% with an error value of 3.57%. The greater the THD percentage value, the greater the reading error on the semi-digital kWh meter and the worse the resulting power factor value. Kata kunci: Non-linear load, kWh Meter, THD